Self-handicapping behavior at work in Indonesia: a case study thematic analysis - Afandi, Ardian Rahman (Titian: Jurnal Ilmu Humaniora, 2023)
Job demands on employees are currently increasingly high. High work intensity is characterized by continuous work. Continuous work tends to drain energy and can make employees burn out. One of the negative behaviors that employees carry out to protect themselves from fatigue and protect their self-esteem is by engaging in self-handicapping behavior. Self-handicapping behavior is a person's behavior to limit or provide reasons related to performance that is not optimal. Researchers want to know the dynamics of employees when carrying out self-handicapping behavior. Data collection for this research was carried out using interviews, but was deepened using questionnaires and observations. This research found that targets are the biggest factor in self-handicapping behavior. Furthermore, support from colleagues is one way for employees to avoid this behavior. Abstrak Tuntutan pekerjaan kepada karyawan saat ini semakin tinggi. Tingginya intensitas pekerjaan ditandai dengan pekerjaan yang dilanjutkan secara berkelanjutan. Pekerjaan yang terus menerus dilakukan cenderung akan menghabiskan tenaga dan dapat membuat karyawan menjadi burnout. Salah satu perilaku negatif yang dilakukan oleh karyawan untuk melindungi diri dari burnout dan juga melindungi self-esteemnya adalah dengan melakukan self-handicapping behavior. Self-handicapping behavior merupakan perilaku seseorang untuk membatasi atau memberikan alasan terkait dengan performa tidak maksimalnya. Peneliti ingin mengetahui dinamika karyawan saat melakukan self-handicapping behavior. Pengambilan data penelitian ini dilakukan menggunakan interview, namun diperdalam menggunakan kuesioner dan observasi. Penelitian ini menemukan bahwa target merupakan faktor terbesar terjadinya self-handicapping behavior. Lebih lanjut, dukungan rekan kerja menjadi salah satu cara karyawan untuk menghindari perilaku ini.